2005
DOI: 10.1007/s00439-005-1333-9
|View full text |Cite
|
Sign up to set email alerts
|

Significant genetic differentiation between Poland and Germany follows present-day political borders, as revealed by Y-chromosome analysis

Abstract: To test for human population substructure and to investigate human population history we have analysed Y-chromosome diversity using seven microsatellites (Y-STRs) and ten binary markers (Y-SNPs) in samples from eight regionally distributed populations from Poland (n = 913) and 11 from Germany (n = 1,215). Based on data from both Y-chromosome marker systems, which we found to be highly correlated (r = 0.96), and using spatial analysis of the molecular variance (SAMOVA), we revealed statistically significant sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 42 publications
12
98
0
1
Order By: Relevance
“…Westward of the Rhine overall R1a1a frequency is low, signaling a genetic boundary with R1b varieties. 39 However, the patterns of currently observed Y-chromosome diversity in East/Central Europe are unlikely to be explained solely by population movements of the last century. 40 Although the median STR haplotype of the derived M458G allele differs from the median type of the ancestral M458A chromosomes at 3 of the 10 STR loci considered in our analyses, the STR data alone are not informative for unambiguous inference of whether an individual has the A or G allele (Supplementary Figures S1 and S2) underscoring the extent of STR saturation and the importance of SNP genotyping to assess phylogenetic ancestry even among closely related lineages.…”
Section: In Situ Diversification In Central Europementioning
confidence: 99%
“…Westward of the Rhine overall R1a1a frequency is low, signaling a genetic boundary with R1b varieties. 39 However, the patterns of currently observed Y-chromosome diversity in East/Central Europe are unlikely to be explained solely by population movements of the last century. 40 Although the median STR haplotype of the derived M458G allele differs from the median type of the ancestral M458A chromosomes at 3 of the 10 STR loci considered in our analyses, the STR data alone are not informative for unambiguous inference of whether an individual has the A or G allele (Supplementary Figures S1 and S2) underscoring the extent of STR saturation and the importance of SNP genotyping to assess phylogenetic ancestry even among closely related lineages.…”
Section: In Situ Diversification In Central Europementioning
confidence: 99%
“…Notably, genetic boundaries were determined to a greater extent by geographic rather than linguistic boundaries, ie, genetic boundaries between Hungary and its neighbors were not significant relative to continental geographic boundaries (Rosser et al, 2000). In separate studies, Poles and Ukrainians were found to share a common patrilineal heritage together with southwestern Russians (Balanovsky et al, 2008) while Poles and Germans were genetically separated according to the present political boundary (Kayser et al, 2005). Nevertheless, intraEuropean selection signatures on AVPR1B have not been studied and thus any correlation with patrilineal boundaries is speculative.…”
Section: Consortium 2010mentioning
confidence: 96%
“…The genetic difference between the Netherlands and Belgium thus increased after 1900 and may be explained by the breakup of the United Kingdom of the Netherlands in these two countries in 1830. As it is observed between Germany and Poland based on Y-chr, 35 administrative borders may affect the current population genetic structure because of the fact that migration occurs mainly within a country. Once there was a notable administrative border between the Netherlands and Belgium, North Brabant received for its textile industry many immigrants from the North where the frequency of R-U106 is relatively high, and the region of Antwerp received more immigrants from the South where this frequency is much lower.…”
Section: Temporal Differentiation Within Brabantmentioning
confidence: 99%